Regulating Access to Firearms - Butryn, Łukasz (Teisė, 2020)
The subject of this article are the legal and criminal aspects of regulating access to firearms. This issue has become extremely important in recent years for sociality. Furthermore, the availability of firearms has been widely discussed in Poland.